2017
DOI: 10.3390/polym9120735
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Assembly of Polyelectrolyte Multilayer onto PET Fabric for Highly Tunable Dyeing with Water Soluble Dyestuffs

Abstract: Poly(ethyleneterephthalate) (PET) is a multi-purpose and widely used synthetic polymer in many industrial fields because of its remarkable advantages such as low cost, light weight, high toughness and resistance to chemicals, and high abrasion resistance. However, PET suffers from poor dyeability due to its non-polar nature, benzene ring structure as well as high crystallinity. In this study, PET fabrics were firstly treated with an alkaline solution to produce carboxylic acid functional groups on the surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(33 citation statements)
references
References 42 publications
(49 reference statements)
1
32
0
Order By: Relevance
“…As seen from wide-scan XPS spectra (Figure 6f), it can be seen almost the same that element C1s (at 283.5 eV) and O1s (at 530.8 eV) were detected on the fiber surface of the three samples. High-resolution C1s XPS analysis that functional groups were same which the element C1s of three samples correspond to characteristics of C–C/C–H (at 284.0 eV), C–O (at 286.0 eV), and O–C=O (at 288.5 eV), respectively (Figure 6g–i) [30,31]. It can be indicated that the cross-linking agent of PETA can be initiated by ammonium persulfate (APS) at proper temperature.…”
Section: Resultsmentioning
confidence: 99%
“…As seen from wide-scan XPS spectra (Figure 6f), it can be seen almost the same that element C1s (at 283.5 eV) and O1s (at 530.8 eV) were detected on the fiber surface of the three samples. High-resolution C1s XPS analysis that functional groups were same which the element C1s of three samples correspond to characteristics of C–C/C–H (at 284.0 eV), C–O (at 286.0 eV), and O–C=O (at 288.5 eV), respectively (Figure 6g–i) [30,31]. It can be indicated that the cross-linking agent of PETA can be initiated by ammonium persulfate (APS) at proper temperature.…”
Section: Resultsmentioning
confidence: 99%
“…To characterize the fabric color attributes, the color of the produced fabrics was measured and quantified using the 7000A spectrophotometer (X-Rite, Incorporated, MI, USA) [22,23]. The colorimetric data expressed by CIE L*, a*, b*, C*, H° values, which represents lightness, red-green component, blue-yellow component, chroma, and hue, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The deconvoluted spectra are shown in Figures S2b, S2c, and S2d. Peak fitting for C1s resulted in two peaks for CÀ C group (at 283.4 eV) and CÀ O group (at 285.1 eV), respectively [32]. The fitting of other two peaks O1s, and N1s resulted in one deconvoluted peak for each core level spectrum which can be assigned as phenolic CÀ OH group (at 531.6 eV), and pyridinic CÀ N group (at 399 eV), respectively [32,33].…”
Section: The Low Magnification Images Frommentioning
confidence: 99%
“…Peak fitting for C1s resulted in two peaks for CÀ C group (at 283.4 eV) and CÀ O group (at 285.1 eV), respectively [32]. The fitting of other two peaks O1s, and N1s resulted in one deconvoluted peak for each core level spectrum which can be assigned as phenolic CÀ OH group (at 531.6 eV), and pyridinic CÀ N group (at 399 eV), respectively [32,33]. These functional groups help towards increasing wettability of the material in solution, facile electrostatic, Van der Waals, and hydrogen bonding interactions with analytes from the solution.…”
Section: The Low Magnification Images Frommentioning
confidence: 99%